Mangrove diversity and suitability assessments for ecotourism in Cimalaya Wetan Coast, Karawang District, Indonesia - Giok Pin Tjiong; Jatna Supriatna; Noverita Dian Takarina; Rudy Parluhutan Tambunan (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Pin TG, Supriatna J, Takarina ND, Tambunan RP. 2021. Mangrove diversity and suitability assessments for ecotourism in Cimalaya Wetan Coast, Karawang District, Indonesia. Biodiversitas 22: 803-810. Mangrove forest has been a popular ecotourism destination recently. One of the methods to assess the mangrove potential for ecotourism is by using Tourism Suitability Index (TSI). This study was aimed to assess the ecotourism potentials of mangrove forest sizing of 56.43 hectares in Cilamaya Wetan Sub-district, Karawang District, West Java Province, Indonesia using the TSI method. To assess the mangrove variables, 10 sampling stations have been selected across the coast. In each station, 10 sample plots sizing of 10 m x 10 m have been established. The TSI was measured based on mangrove variables including species diversity, density, and thickness. We recorded six mangrove plant species belonging to three plant families. Avicennia alba, Bruguiera gymnorrhiza and Rhizophora stylosa, were common species found along the coast. Shannon-Wiener index (H’) showed that the west and east parts of Cimalaya Wetan had high mangrove diversity compared to the central part. The TSI analysis showed that the most suitable areas of mangrove forests for ecotourism were 32.18 hectares (57.11% of the total area), mainly located in the east part of the coast. Moreover, the moderate and least suitable areas were 19.12 hectares (33.94%) and 5.03 hectares (8.93%), respectively, and located in the central part of the coast.